Airflow obstruction, atherosclerosis and cardiovascular risk factors in the AGES Reykjavik study - Gudmundsson, Gunnar (Atherosclerosis, 2016)
BACKGROUND AND AIMS: Airflow limitation, i.e. reduced forced expiratory volume in one-second (FEV1) is associated with increased prevalence of atherosclerosis, however, causal mechanisms remain elusive. The objective of the study was to determine if the association between airflow obstruction and markers of atherosclerosis were mediated by systemic inflammation. METHODS: 1154 subjects from the longitudinal AGES Reykjavik study were included. Population characteristics, systemic inflammation markers from blood (white blood cell counts (WBC) and level of C-reactive protein (CRP)) were compared between patients with and without airflow limitation defined by reduced FEV1 on spirometry. Atherosclerosis burden was quantified by measurements of coronary artery calcium, aortic arch and distal aortic calcification in addition to carotid intimal media thickness (CIMT). RESULTS: Subjects were split into four groups according to smoking status and if airflow limitation was present. There was a higher overall burden of atherosclerosis in ever-smokers compared to never-smokers, and in individuals with airflow obstruction compared to individuals without airflow obstruction. After adjusting for population characteristics, Framingham cardiovascular risk factors and markers of systemic inflammation (WBC and CRP), there was a significantly more aortic arch and distal aorta calcification and higher measurement of CIMT for individuals with airflow obstruction compared to individuals without airflow obstruction. After adjusting for population characteristics, Framingham cardiovascular risk factors and markers of systemic inflammation (WBC and CRP), there was a significantly more aortic arch and distal aorta calcification and higher measurement of CIMT for individuals with airflow obstruction compared to individuals without airflow obstruction. CONCLUSIONS: Systemic inflammation (WBC and CRP) does not appear to mediate the association between airflow limitation and atherosclerosis. Only airflow limitation and not systemic inflammation (WBC and CRP) appears to be an independent predictor of atherosclerosis.